PENGARUH LIMBAH BIOGAS SAPI TERHADAP KETERSEDIAAN HARA MAKRO-MIKRO INCEPTISOL - Utami, Sari Widya; Sunarminto, Bambang Hendro; Hanudin, Eko (Jurnal Ilmu Tanah dan Air)
Objective of this research to know the effect of cattle sludge application on N, P, K, Fe, Mn, Zn and Cu availability of Inceptisol that had been cultivated intensify. Cattle sludge that used, consisted by 2 form; solid and liquid (slurry) form. The experiment was arranged Completely Block Randomized Design (CRBD) with 3 replicates of 2 factors combination. The first factor was dose of solid sludge consisted 2 leves were 0 ton/ha (P0) and 5.4 ton/ha (P1). The second factor was dose of slurry consisted 4 levels, were 0 liter/ha (D0), 500 liter/ha (D1), 1000 liter/ha (D2), 1500 liter/ha (D3). Variables were observed some soil chemical characteristic such as pH, EC, Corganic, CEC, total N, availability of P, availability of K, availability of Fe, availability of Mn, availability of Zn and availability of Cu. Data were analysed by F test and if there were significant effect then continued by using Duncanâs Multiple Range Test (Î± = 5%). Result of this research showed gave solid sludge as much 5.4 ton/ha was able to increase pH, Corganic and total N. Gave slurry was not able to increase macro and micro nutrient availability of Inceptisol